The Polar Express [videorecording (Blu-Ray)] - Starkey, Steve; Zemeckis, Robert, 1952-; Goetzman, Gary, 1952-; Teitler, William; Broyles, William, Jr., 1944-; Hanks, Tom; Zemeckis, Leslie Harter; Deezen, Eddie, 1957-; Gaye, Nona; Scolari, Peter, 1955-2021; King, Brendan; Pellick, Andy; et al. (Distributed by Warner Home Video, 2007)
Billy longs to believe in Santa Claus, but he finds it quite difficult to do so. His family has a dogged insistence that all of it, from the North Pole, to the elves, to Santa himself, is all just a myth. This all changes, however, on Christmas Eve, when a mysterious train visits Billy in the middle of the night, promising to take him and a group of other lucky children to the North Pole for a visit with Santa. The train's conductor, along with the other passengers help turn Billy's crisis of faith into a journey of self-discovery.